Deep Minimum and a Vortex for Positronium Formation in Low-Energy Positron-Helium Collisions - Albandari W. Alrowaily; Sandra J. Ward; Peter Van Reeth (Atoms, 2021)
We find a zero in the positronium formation scattering amplitude and a deep minimum in the logarithm of the corresponding differential cross section for positron–helium collisions for an energy just above the positronium formation threshold. Corresponding to the zero, there is a vortex in the extended velocity field that is associated with this amplitude when one treats both the magnitude of the momentum of the incident positron and the angle of the scattered positronium as independent variables. Using the complex Kohn variational method, we determine accurately two-channel K-matrices for positron–helium collisions in the Ore gap. We fit these K-matrices using both polynomials and the Watanabe and Greene’s multichannel effective range theory taking into account explicitly the polarization potential in the Ps-He+ channel. Using the fitted K-matrices we determine the extended velocity field and show that it rotates anticlockwise around the zero in the positronium formation scattering amplitude. We find that there is a valley in the logarithm of the positronium formation differential cross section that includes the deep minimum and also a minimum in the forward direction.